Study the Relationship between ABO Blood Groups and Gingivitis Disease - Bushra Habeeb; Tamara Ala`a; Hayfa`a Jaber (Kufa Journal for Nursing Sciences)
Objectives: Design this study to determine whether there was a relationship between gingival diseases and ABO blood groups.